Evidences for ecological niche differentiation on the Anatolian lizard (Apathya cappadocica ssp.) (Reptilia: Lacertidae) in western Asia - Hosseinian Yousefkhani, Seyyed Saeed; Wink, Michael (Biologia, 2019)
The aim of this study was to predict suitable habitat for different clades of Apathya cappadocica in the Middle East. An additional goal was to calculate the ecological niche space of all lineages to determine the hypothesized degree of niche overlap and niche differentiation between these clades in Iran, Turkey, Iraq and Syria. All presence records of Apathya taxa in the study area were obtained and georeferenced from fieldwork, literature, and museums. All presence points were determined using 1 x 1 km grids covering the study countries. Environmental data such as bioclimate variables were also gathered at this resolution. Species distribution modeling was carried out using MaxEnt to determine current suitable regions for each lineage, and then the outputs were compared to find the degree of niche overlap between them. Our results found that all of the predicted models have high accuracy and some overlap with each other, especially for A. c. schmidtlerorum, but other lineages have distinctive models. Mean temperature of coldest quarter, isothermality, annual precipitation, and precipitation of coldest quarter were the highest contributed variables for A. c. cappadocica, A. c. wolteri, A. c. schmidtlerorum, A. c. urmiana, and A. c. muhtari, respectively. Ecological niche differentiation was found between all lineages, but A. c. schmidtlerorum shows niche similarity with other subspecies. Therefore, as previously recommended, A. c. schmidtlerorum can be synonymized with A. c. muhtari. Finally, our ecological results confirmed the specific status of all genetic lineages except for A. c. schmidtlerorum, consistent with the recommendation from a previous molecular study.